Respuesta :
Answer:
[tex] \boxed{ \boxed{ \sf{ \bold{( x - 7)(x + 3)}}}}[/tex]
Step-by-step explanation:
[tex] \sf{ {x}^{2} - 4x - 21}[/tex]
Here, we have to find the two numbers that subtracts to 4 and multiplies to 21
⇒[tex] \sf{ {x}^{2} - (7 - 3)x - 21}[/tex]
⇒[tex] \sf{ {x}^{2} - 7x + 3x - 21}[/tex]
Factor out X from the expression
⇒[tex] \sf{ x(x - 7) + 3x - 21}[/tex]
Factor out 3 from the expression
⇒[tex] \sf{x(x - 7) + 3(x - 7)}[/tex]
Factor out x-7 from the expression
⇒[tex] \sf{(x - 7)(x + 3)}[/tex]
Hope I helped!
Best regards!!
Answer:
[tex]\boxed{\boxed{\bold{(x - 7)(x + 3)}}}[/tex]
Step-by-step explanation:
[tex] {x}^{2} - 4x - 21 \\ {x}^{2} - 7x + 3x - 21 \\ x(x - 7) + 3(x - 7) \\ (x - 7)(x + 3)[/tex]